Análise do processo anafórico em textos produzidos por alunos do terceiro ano do ensino médio de uma escola pública de Cascavel- PR. - Bernardi, Eviliane (2012)
This research aims to investigate the referentiation process performed by the recategorization coreferential anaphora and non-coreferential in texts belonging to the school essay genre, produced by students of the High School third year of a public school in Cascavel PR and we intend to investigate how the producer of the text deals with the process of recovery, (re) constructing discourse objects, that allow verifying judgments and argumentative proposals of the producer. For this, we proceeded to the selection and analysis of the corpus constituted by texts produced by students of the High School third year of a public school in Cascavel PR. The research is guided by works of authors based on the sociocognitive interactionist language conception, who consider the language as a form of socio-historical cognition and of interactive character, as Mondada e Dubois (2003), Koch (2005), Marcuschi (2007a, 2007b, 2007c), Apothéloz e Reichler-Béguelin (1995, 1999). We observed that the referential expressions contribute to elaborate the meaning, indicate points of view, point out argumentative directions, and act in the progression and textual cohesion. We noted that the lexical elements selection in the text represent ways of understanding not only the subject in the classroom but also evaluation linked to a discursive project of the speakers. We consider this study important for teaching, because it contributes to the teacher, considering that the referentiation process can assist in the construction of the argumentation, develop the language proficiency of students to the textual production.